The role of connectivity in significant bandgap narrowing for fused-pyrene based non-fullerene acceptors toward high-efficiency organic solar cells. Issue 12 (10th March 2020) - Liu, Shungang; Su, Wenyan; Zou, Xianshao; Du, Xiaoyan; Cao, Jiamin; Wang, Nong; Shen, Xingxing; Geng, Xinjian; Tang, Zilong; Yartsev, Arkady; Zhang, Maojie; Gruber, Wolfgang; et al.
Abstract : Isomers of non-fullerene acceptors with pyrene as cores but fused at different positions were studied. FPIC6 possessed ∼119 nm of red-shift absorption and much higher power conversion efficiency of 11.55% as compared to its structural isomer FPIC5. Abstract : Great attention has been paid to developing low bandgap non-fullerene acceptors (NFAs) for matching wide bandgap donor polymers to increase the photocurrent and therefore the power conversion efficiencies (PCEs) of NFA organic solar cells, while pyrene-core based acceptor–donor–acceptor (A–D–A) NFAs have been mainly reported via the 2, 9-position connection due to their bisthieno[3′, 2′- b ']thienyl[ a, h ]pyrene fused via a five-membered ring bridge at the ortho-position of pyrene as the representative one named FPIC5, which has prohibited further narrowing their energy gap. Herein, an acceptor FPIC6 was exploited by creating the 1, 8-position connection through fusing as bisthieno[3′, 2′- b ′]thienyl[ f-g, m-n ]pyrene linked at the bay-position via a six-membered bridge, with enhanced push–pull characteristics within such A–D–A structure. As a structural isomer of FPIC5, FPIC6 exhibited a much lower bandgap of 1.42 eV (1.63 eV for FPIC5 ). Therefore, the photocurrent and PCE of PTB7-Th :FPIC6 cells were improved to 21.50 mA cm −2 and 11.55%, respectively, due to the balanced mobilities, better photoluminescence quenching efficiency and optimized morphology, which are both ∼40% better than those of PTB7-Th :FPIC5 cells. Our results clearly proved that a pyrene fused core with 1, 8-position connection with electron-withdrawing end groups instead of 2, 9-position connection is an efficient molecular design strategy to narrow the optical bandgap and improve the photovoltaic performance of NFA based OSCs.